Penerapan Hukuman Mati Bagi Pelaku Residive Tindak Pidana Peredaran Narkotika (STUDI KASUS PERKARA NOMOR 254/PID.SUS/2024/PN PDG) - Liza Puspita; Engrina Fauzi (CV. ITTC INDONESIA, 2026)
The illegal distribution of narcotics in Indonesia has reached a critical point, posing a threat to national stability, public health, and the future of the younger generation. This type of crime is extremely dangerous, so the actions taken must be firm, structured, and based on justice. One form of law enforcement that has received attention is the application of the death penalty, especially for perpetrators who have previously been involved in similar crimes and have served their sentences. This study legally explores the decision of the Padang District Court in case number 254/Pid.Sus/2024/PN Pdg, in which a life sentence was given to the defendant, a recidivist, as an alternative to the death penalty. The legal basis used includes Law Number 35 of 2009 concerning Narcotics, specifically Article 114 paragraph (2), as well as provisions in the Criminal Code (KUHP) and other related laws and regulations. The state is making efforts to eradicate the illicit distribution of narcotics with various approaches, not only through repressive criminal law, but also with preventive, educational, and rehabilitative approaches to protect society, especially the younger generation. The problems discussed in this research are: (1) How does Indonesian positive law regulate the death penalty for recidivists in narcotics trafficking cases?; (2) How effective is the death penalty compared to life imprisonment in preventing recidivism in case 254/Pid.Sus/2024/PN Pdg?; and (3) How does the application of the death penalty compare to countries with civil law systems? The purpose of this study is to legally analyze the application of the death penalty to recidivists in narcotics crimes and to evaluate the legal considerations used by the panel of judges in imposing a life sentence instead of the death penalty, as well as to compare the death penalty with countries that adopt a civil law system. The method used is a normative method with a legislative and case approach, and data collection through literature studies on laws and regulations, legal literature, and court decision documents. The research concludes that drug trafficking, particularly by repeat offenders, poses a serious threat to national security that cannot be optimally addressed. Therefore, a balance is needed between the objectives of punishment and the principle of justice in the implementation of criminal law in Indonesia.